A Probe into the Introduction of British and American Culture in the Teaching of English Majors Based on Computer Assisted Technology. Issue 3 (October 2020) - Qu, Ying
Abstract: With the development of globalization, communication between countries is becoming more and more frequent. Since English is one of the most commonly international languages, Chinese students have been offered English courses at all stages. In the course of English reading, English major students are often restrained by cultural differences. In order to solve this problem effectively, teachers should actively introduce British and American culture so that students can understand articles better and then constantly improve their English reading ability. Therefore, this article will briefly explain British and American culture based on computer-assisted technology combined with some personal English learning experience. The importance of introduction lies in the teaching of English reading, and its content and methods are intended to provide readers with some help.